Coronary CT angiography: a guide to examination, interpretation, and clinical indications. (4th May 2021) - Cademartiri, Filippo; Casolo, Giancarlo; Clemente, Alberto; Seitun, Sara; Mantini, Cesare; Bossone, Eduardo; Saba, Luca; Sverzellati, Nicola; Nistri, Stefano; Punzo, Bruna; Cavaliere, Carlo; La Grutta, Ludovico; et al.
ABSTRACT: Introduction: The introduction of Cardiac Computed Tomography (CCT) has changed the paradigm in the field of diagnostic cardiovascular medicine. CCT is the primary tool in the assessment of suspected Coronary Artery Disease (CAD) and should be followed by functional assessment when needed to stratify disease and to plan potential interventional or surgical therapy. Areas Covered: We provided the current state of the knowledge on the main aspects of technique of examination, image interpretation and clinical indications. We have focused our attention on the basic routine applications and activities. Expert Opinion: The primary role of CCT in suspected CAD will progressively become the standard approach. In general, any situation in which anatomy of the heart and thoracic vessels/structures is mandatory must be approached using CT first, whenever possible. The quantity and quality of information that can be provided by CCT is big and the operators should learn how to deal with this information. On the other hand, CCT is only apparently a straightforward and simple examination. It is actually the most complex diagnostic procedure that can be performed on CT and requires highly skilled operators and state-of-art-technology.